Establishment of an experimental model of small intestinal ischemia and reperfusion injuries in New Zealand rabbits - Alvaro P.L. Oliveira; Julia P.P. Rangel; Luiz F.S. Riodades; Bruna L. Almeida; Carlos Henrique T. Mathias; Laura M.C. Conti; Wagner A.B. Fiorio; Betânia S. Monteiro (Pesquisa Veterinária Brasileira)
ABSTRACT: The present study aimed to establish a methodology capable to cause intestinal ischemia and reperfusion injuries, to perform clamping of the jejunal segment of the extramural peri-intestinal marginal artery branch. For this, 37, 10-week-old male New Zealand breed rabbits were used. One rabbit was used to establish the anatomic references for the procedure and was not part of the six experimental groups; the rest were allocated into six experimental groups: Sham group, negative control, subjected only to midline celiotomy; group I1H undergoing vascular occlusion for an hour; group I2H submitted to vascular occlusion for two hours; group I1H/R2H undergoing vascular occlusion for one hour followed by two hours of reperfusion; group I2H/R1H undergoing vascular occlusion for two hours, followed by reperfusion for one hour, and group I2H/R5H undergoing vascular occlusion for two hours followed by reperfusion for five hours. The rabbits were evaluated for the macroscopic aspects (color and peristalsis) of the jejunal segment, as well as the histological aspect, checking for presence or absence of mucosal destruction, edema, hemorrhaging, lymphatic vessel dilatation, and the presence of polymorphonuclear cells. It was observed that the macroscopic and histopathological lesions accentuated in larger employed ischemia and reperfusion times. Rabbits subjected to ischemia for two hours followed by reperfusion for five hours (I2H/R5H) made up the experimental group which was easily reproducible and showed moderate intestinal injury, different from the other groups.